Upaya Pencegahan White Collar Crime - Heni Winda Siregar; Nadila Kirani; Dea Annisa Br Tarigan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
White collar crime is increasingly prevalent in various corporate sectors and causes significant financial losses and damage to public trust. This type of crime includes embezzlement of funds, manipulation of financial statements, bribery, insider trading in the capital market, and theft of customer personal data. Although it occurs a lot, the prevention of white collar crime is still not optimal and the perpetrators are rarely prosecuted properly. This paper aims to analyze the various determinants that influence the occurrence of white collar crime in order to formulate policy recommendations and prevention strategies in the future. A systematic approach is used by applying the fraud triangle theory which focuses on the three main elements that cause fraud, namely pressure, opportunity and rationalization. The results of the study show that pressure to meet high performance targets and large bonuses often encourage individuals to commit fraud. Meanwhile, weak supervision and lack of transparency create opportunities for fraud. Perpetrators also often justify their actions, for example by assuming that they will not be caught or the value of the loss is small. The complexity of modern corporate operations also increases opportunities for white-collar crime. Effective prevention efforts must be comprehensive by involving various parties and strengthening a number of aspects as controls. The role of internal and external supervisors (auditors) of companies needs to be continuously improved, supported by modem fraud detection technology tools. Whistleblowing mechanisms need to be strengthened in every company and kept confidential to encourage early reporting of fraud indications.